2015
DOI: 10.3168/jds.2014-8347
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes in freestall-housed dairy cows with naturally occurring clinical mastitis

Abstract: Dairy cows exhibit classic signs of sickness behavior during mastitis. However, knowledge about the consequences of naturally occurring mastitis in freestall-housed dairy cows, milked in automatic milking systems, is lacking. The aim of the present study was to describe the behavior of dairy cows after diagnosis and antibiotic treatment of mastitis. In the days before and after antibiotic treatment, the milking behavior, feeding, and activity were examined in 30 mastitic and 30 control Danish Holstein-Friesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 26 publications
5
75
0
Order By: Relevance
“…This oversimplifies the potential effect of DCT on development of antimicrobial resistance, public opinion on preventive antimicrobial usage, political issues, and animal welfare. Although the perspective of animal welfare differs between citizens and farmers (Vanhonacker, 2008), mastitis, specifically CM, does affect animal welfare (Fogsgaard et al, 2015). Finally, for a system such as a selection protocol for DCT to be successfully implemented in practice, its applicability is important.…”
Section: Discussionmentioning
confidence: 99%
“…This oversimplifies the potential effect of DCT on development of antimicrobial resistance, public opinion on preventive antimicrobial usage, political issues, and animal welfare. Although the perspective of animal welfare differs between citizens and farmers (Vanhonacker, 2008), mastitis, specifically CM, does affect animal welfare (Fogsgaard et al, 2015). Finally, for a system such as a selection protocol for DCT to be successfully implemented in practice, its applicability is important.…”
Section: Discussionmentioning
confidence: 99%
“…This condition affects almost 25% of the 9.3 million dairy cows present in the USA every year [3] and negatively impacts animal welfare [46] and productivity [79]. Recent studies have reported that approximately 80% of all antimicrobials used on American dairy farms are for the treatment or prevention of mastitis [10].…”
Section: Introductionmentioning
confidence: 99%
“…The current study used 1 d to record behavioral observations within each period, as this was the only day allowing for 24 h of uninterrupted observation. Many factors can influence the day-to-day variation in dairy cow behavior, including social structure (Grant and Albright, 2001), estrus cycles (Halli et al, 2015, Pahl et al, 2015, and disease (Fogsgaard et al, 2015). To help mitigate these variations, the study allowed 9 d to acclimate to the pens and establish a hierarchy, although cow feeding behavior was only affected during the 1 h after the first fresh feed delivery after regrouping (von Keyserlingk et al, 2008).…”
Section: Short Communicationmentioning
confidence: 99%